(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article analyzes the applied arts of the Surkhan oasis, particularly the traditions of craftsmanship, based on historical sources. The place of handicraft activity in the cultural life of the oasis population, its ethnographic features, and the current state are highlighted with a deep scientific approach.